ASSOCIATION OF HYPERTENSION AND DIABETES MELLITUS WITH HEART DISEASE AMONG OLDER ADULTS IN INDONESIA - Nawangwulan, Tama Mega; Asri, Yuni; Fani, Rif'atul; Rizzal, Alfunnafi Fahrul (HEARTY, 2026)
Background: Cardiovascular disease remains a leading cause of morbidity and mortality among older adults, particularly in low- and middle-income countries experiencing rapid population aging. Hypertension and diabetes mellitus are common chronic conditions in later life and are well-established risk factors for heart disease. However, nationally representative evidence examining their associations with heart disease among older adults in Indonesia remains limited. Objective: This study aimed to examine the association between diagnosed hypertension and diagnosed diabetes mellitus with diagnosed heart disease among older adults in Indonesia. Methods: A descriptive correlational study with a cross-sectional design was conducted using secondary data from the 2023 Indonesian Health Survey (Survei Kesehatan Indonesia/SKI). The study included older adults aged ≥60 years with complete data on hypertension, diabetes mellitus, and heart disease. Data were analyzed using univariate analysis to describe variable distributions and bivariate analysis using the Chi-square test to assess associations. Statistical significance was set at p < 0.05. Results: Among 97339 older adults, the prevalence of hypertension was 21.9%, and diabetes mellitus was 6.1%. Heart disease was more prevalent among older adults with hypertension and diabetes mellitus compared to those without these conditions. Both hypertension and diabetes mellitus were significantly associated with heart disease (p < 0.001). Conclusion: Hypertension and diabetes mellitus are significantly associated with heart disease among older adults in Indonesia. These findings highlight the importance of integrated chronic disease prevention and management strategies targeting older populations to reduce the burden of cardiovascular disease.